Dynamic principles of the microbiome and the bovine vagina: a review - Dias, Nicholas Wege; Poole, Rebecca; Soffa, Dallas R.; Brown, Kyle Joel Hickman (Frontiers in Microbiology, 2024)
The role of microbes inhabiting various body sites in supporting host physiology and health is substantial, and recent advancements in DNA sequencing technology have facilitated a more in-depth understanding of these microbial contributions. The influence of microbiota within a given organ can be broadly categorized as having two main functions: (1) promoting organ homeostasis and (2) creating conditions that inhibit the growth of pathogenic microorganisms, thereby protecting the host from diseases. In livestock production, numerous phenotypes critical to industry outcomes are affected by the microbiome, which has sparked considerable academic interest in recent years. This review aims to analyze the extensive data available on the microbiomes of humans and other mammalian species, examining microbiome ecology to elucidate principles that may assist in interpreting data on livestock microbiomes. Additionally, the review will discuss techniques available for investigating various microbiome aspects and will examine existing data on the reproductive microbiome, with a particular focus on the bovine vaginal microbiome.